THE ROLE OF PUBLIC PARTICIPATION IN ADDRESSING ECOLOGICAL ISSUES IN OUR REPUBLIC (TAMADDUN NURI JURNALI, 2025)
This article explores the role of public participation in solving ecological problems in Uzbekistan, the activities of civil society institutions, ways to strengthen cooperation between the state and society, as well as an analysis of national and international experiences